Enhanced Brightness and Device Lifetime of Quantum Dot Light‐Emitting Diodes by Atomic Layer Deposition. Issue 12 (27th May 2020) - Kim, Gi‐Hwan; Noh, Kyeongchan; Han, Jisu; Kim, Minsu; Oh, Nuri; Lee, Woongkyu; Na, Hyon Bin; Shin, Chansun; Yoon, Tae‐Sik; Lim, Jaehoon; Cho, Seong‐Yong
Abstract: Colloidal quantum dot light‐emitting diodes (QD‐LEDs) are one of the future emissive displays, but understanding charge transport mechanism at the interface and improving charge balances in the device are key challenges to the commercialization of QD‐LED. In this study, the ZnO interlayer is introduced by atomic layer deposition (ALD) technique to enhance the performance and lifetime of green‐emitting CdZnSeS/ZnS core/shell QD‐LEDs. Atomic force microscopy images of QD layer reveal that the thin film of ZnO deposited by ALD reduces the root‐mean‐square (RMS) roughness of the QD film to less than 2 nm, even though the average diameter of the individual QDs is about 10.9 nm, which results in the suppression of excess electron transport in QD‐LED devices. The enhanced performance (an improvement of maximum luminescence from 70 000 to 160 000 cd m −2 ) and operational stability (an improvement of operation lifetime from 20 to 61.5 h at 5000 cd m −2 ) of the QD‐LEDs result from the formation of the smoother interface between the QD and electron transport layers, which is indicated by deposition of thicker ALD ZnO or deposition of ALD ZnO after coating the ZnO nanoparticles as an electron transport layer. Abstract : Atomic layer deposited ZnO interlayer is deposited as an interfacial layer in quantum dot light‐emitting diode (QD‐LED) devices. The enhanced performance (an improvement of maximum luminescence from 70 000 to 160 000 cd m −2 ) and operational stability (operation lifetime from 20 to 61.5 h at 5000 cd m −2 ) are achieved due to better interface between QD and other functional layers.